A Study on Parental Awareness Regarding ROP Eye Screening and Follow-Up Compliance in Infants Diagnosed with Retinopathy of Prematurity at A Tertiary Eye Care Centre in Northern India - Sinha, Madhulika; Anand, Abhishek; Kumar Karn, Manish (Journal of Neonatal Surgery, 2025)
Background: Retinopathy of Prematurity (ROP) causes preventable childhood blindness in preterm babies. Vision loss prevention requires timely screening and follow-up. Parental awareness is crucial to eye care compliance. In Northern India, insufficient parental knowledge and socio-economic challenges delay follow-up, increasing the likelihood of vision-threatening disorders. Method: This 1-year retrospective, hospital-based study was undertaken at the Regional Institute of Ophthalmology (RIO), IGIMS, Patna (April 2024–March 2025). 200 ROP-diagnosed infant parents were questioned using a systematic and validated questionnaire. Demographics, ROP awareness, screening and follow-up knowledge, information sources, and follow-up challenges were collected. For clarity, questions were held in Hindi/Magahi. Descriptive statistics summarised data, and Chi-square tests and other inferential analysis examined awareness levels and socio-demographic characteristics. Results: Of the 200 participants, only 39% were aware of ROP before initial screening. Most common sources of awareness included neonatologists (45%) and healthcare staff. Follow-up compliance was observed in 71% of infants, with dropouts largely due to financial burden (26%), lack of understanding (22%), and transportation issues (19%). A significant correlation was found between parental education and ROP awareness (p < 0.01). Income level also influenced compliance. Barriers to follow-up were more prominent among parents with low literacy and from rural areas. Conclusion: The study emphasizes the need for targeted parental education programs within NICUs and the incorporation of structured follow-up reminder systems to improve ROP screening compliance. Community health workers must be trained to reinforce awareness at the grassroots level. Interventions addressing socio-economic and logistical challenges are vital to reduce preventable blindness due to ROP. Multi-centric and longitudinal studies are recommended to validate and scale effective strategies.